Homesteading on the plains daily life in the land of Laura Ingalls Wilder - Wade, Mary Dodson; Wilder, Laura Ingalls 1867-1957.; Dunn, Harvey 1884-1952. (Brookfield, Conn. : Millbrook Press, 1997)
Quotes from the writings of Laura Ingalls Wilder and paintings by one of her relatives accompany accounts of pioneer life in the Midwest during the second half of the 1800s.
Includes bibliographical references
Keywords: Wilder, Laura Ingalls -- 1867-1957 -- Homes and haunts -- Juvenile literature. -- Great Plains; Wilder, Laura Ingalls -- 1867-1957 -- Homes and haunts; Women authors, American -- Biography -- Juvenile literature. -- 20th century; Frontier and pioneer life -- Juvenile literature. -- Great Plains; Frontier and pioneer life -- Great Plains